Analisis Kesadaran Diri Dan Motivasi Belajar Terhadap Disiplin Belajar Mahasiswa Program Studi Manajemen Di Universitas Perjuangan Tasikmalaya - Andika Agung S; Suci Putri Lestari; Nita Fauziah Oktaviani (MUQADDIMAH: Jurnal Ekonomi, Manajemen, Akuntansi dan Bisnis, 2023)
This study aims to identify and analyze the influence of self-awareness and learning motivation on student learning discipline in the Management Study Program at the University of Perjuangan, Tasikmalaya. The method used in this research was causality through a survey approach, with a research sample of 100 students of the Management Study Program at the University of Perjuangan, Tasikmalaya. The data used uses primary data. The analytical tool used in this research is multiple regression using SPSS 26. The results show that Self-awareness has a good classification, Learning Motivation has a good classification, and Learning Discipline has a good classification for Students of the Management Study Program at the University of Perjuangan Tasikmalaya. Simultaneously Self-Awareness and Learning Motivation have a significant influence on Learning Discipline. Partially Self-Awareness has a significant influence on Learning Discipline. Partially, learning motivation has a significant influence on learning discipline in students of the Management Study Program at the University of Perjuangan, Tasikmalaya.